The Penitente Papers - Aranda, Charles frey50 (Albuquerque, NM Charles Aranda)
Correspondence, chants.
Two copies in files - both labeled #3 - one copy with Dewey 265.63 A and acession #42875, formerly on shelves.
Keywords: Penitentes - New Mexico -- 1946 - 1951 - Correspondence concerning incorporation of the Franternity of Our Lord Jesus the Nazarene and Rules and Consitution approved in 1951. -- Correspondence and Minutes of Archbishops Supreme council meetings 1952 - 1954. -- 1954 1959 Pastoral Letters from Archbishop - Book of Regulations of Council fo Sangre de Cristo. -- 1960 - Death of Archbishop Byrne - Correspondence of Archbishops Supreme Council . -- Exercise of the Good Death - 1885. -- Penitente Chants. -- Preambulo y La Hermanidad